THE IMPACT OF CHILD-FRIENDLY LIBRARIES ON EDUCATIONAL BEHAVIOR OF ELEMENTARY SCHOOL STUDENTS IN TEGAL REGENCY - Rullis, Rullis; Muljani, Sutji (PIONIR: JURNAL PENDIDIKAN, 2026)
The low reading interest among elementary school students in Indonesia is a critical issue, often exacerbated by school library conditions that are rigid, non-ergonomic, and visually unappealing. This study aims to deeply analyze the impact of child-friendly library interior design innovations on the formation of educational behavior among students in Tegal Regency. This research serves as a response to the "unattractive" library phenomenon by proposing a holistic design intervention. Using a qualitative approach with an instrumental case study design, the research was conducted in three elementary schools participating in the National Child-Friendly Library program: SD Negeri Rangimulya, SD Negeri Dampyak 02, and SD Negeri Procot 03. Data were collected via triangulation techniques, including participatory observation, structured interviews with principals, teachers, and students, and extensive documentation. The data were then analyzed using the Miles and Huberman interactive model. The results indicate that interior design transformations focusing on three core elements physical (vibrant colors, zoning, ergonomic furniture), environmental (lighting, ventilation), and inclusivity successfully created a more stimulating, safe, and comfortable library atmosphere. This spatial transformation significantly impacted students' educational behaviors in multidimensional ways. First, there was a surge in Independent Visit Initiatives, indicating a shift from passive to active literacy interest. Second, Persistence and Focus improved, evidenced by longer durations of reading time ("time on task") facilitated by comfortable seating options like bean bags and carpets. Third, Positive Social Interaction flourished, where the library became a hub for collaborative learning and discussion, fostering mutual respect. Fourth, Curiosity and Exploration were heightened through accessible low-shelving and thematic visual displays. It is concluded that library interior design serves not merely as an aesthetic improvement, but as a vital pedagogical instrument. The child-friendly design effectively bridges the gap between students and literacy, transforming the library from a mere storage room into a vibrant center for character building and educational development. Keywords: Interior Design, Child-Friendly Library, Educational Behavior, Reading Interest, Elementary School, Literacy Environment.